P-28 Staff experiences of delirium in the hospice setting. (1st March 2017) - Waterfield, Kerry; Kiltie, Rachel; Pickard, Jonathan; Karandikhar, Ulka; MacCormick, Fiona; Weiand, Donna; Dewhurst, Felicity; Vidrine, Jen; Rowley, Grace; Coulter, Paul
Abstract : Background: Delirium affects up to 88% of patients with advanced cancer and is associated with significant morbidity and mortality. Despite this it remains under recognised in hospice settings and the management is not always in line with national guidelines. This research study explores the views of staff nurses and healthcare assistants in hospices in order to identify underlying reasons for this. Method: Semi-structured qualitative interviews were conducted with registered nurses (12) and healthcare assistants (6) in three North-East England hospices. Data was analysed using interpretative phenomenological analysis. Results: The main themes to emerge were knowledge and management. Data highlight that knowledge of delirium is variable leading to uncertainty about what constitutes delirium in hospice inpatients with subsequent difficulties in management. Subthemes in management include the emotional response evoked by caring for patients with delirium, ensuring patient safety within the hospice environment and staff perceptions about the appropriate place of care. Disparities in staff opinion are apparent between drug and non-drug approaches and there is also concern about the possible effects of medication. Conclusion: Results from three different hospices across the North East region consistently highlight similar barriers to the assessment and management of delirium. The data provides valuable insights which help to guide future staff education and multidisciplinary team working in order to improve the care of patients with delirium.